Inequity in awareness and utilization of adolescent reproductive and sexual health services in union territory, Chandigarh, North India - Madhu Gupta; Nidhi Bhatnagar; Pankaj Bahugana (Wolters Kluwer Medknow Publications, 2015)
Background: Adolescents are a heterogeneous, vulnerable, and sexually active group. Geographical and educational health disparities exist among urban, rural, and slum adolescents and among out-of-school and school-going adolescents, respectively. Adolescent reproductive and sexual health (ARSH) services should be implemented in a manner to minimize health inequities among them. Objectives: To ascertain the extent of awareness and utilization of ARSH services provided under reproductive and child health(RCH) program among adolescents in Chandigarh. Materials and Methods: A cross-sectional study was conducted among 854 adolescents (402 household, 200 out-of-school, and 252 school-going adolescents) in Chandigarh using pretested validated interview schedule on awareness and utilization of adolescent reproductive and sexual health services from February to April 2011 in North Indian Union Territory of Chandigarh. Ordinal regression analysis was done to study the association of socio-demographic variables with awareness and utilization of ARSH. Results: Awareness about contraception and health services was significantly less among rural (12.7% and 1.1%, respectively) adolescents as compared to slum (17.9% and 4.6%, respectively) and urban adolescents (33.5% and 7.8%, respectively) (P < 0.05). Out-of-school adolescents were utilizing the preventive [odds ratio (OR) 0.39, P < 0.001] and curative services significantly lesser (OR = 0.54, P < 0.001) and had higher substance abuse (OR = 4.26, P= 0.006). Awareness was significantly associated with older age of adolescents (OR = 4.4,P < 0.001), poor education of father (OR = 0.5, P = 0.002), rural area (OR = 0.56, P = 0.001), and out-of-school status (OR = 0.35, P < 0.001). Conclusion: Awareness and utilization of ARSH services was inequitable and was more among urban and school-going adolescents. Educational status was the most important factor affecting it.